Model nowosądecki w edukacji muzycznej = Model nowosądecki in music education - Raszke, Bożena; Enzinger, Grażyna (Zielona Góra ; Skarbona: Stowarzyszenie Polskich Muzyków Kameralistów)
The authors presented in the text prepared on the basis KKPM new model of music education called by Model Nowy Sącz. Made characteristics of the foundation of this model and also presented its practical aspect. This solution is proposed action, combining his musical education with a broad cultural context. Serve it also has the dissemination of the concept and to emphasize its availability for everyone.
Keywords: treści muzyczne; doświadczenia i umiejętności muzyczno-metodyczne; kontekst aktualności; rodzaje aktywności muzycznej; kategorie estetyczne; zapis muzyczny; musical contents; experience and skills of music and methodical; contexts news; types of musical activity; aesthetic categories; musical notation